Anxiety Factors in Doing Floor Gymnastics (Front Roll) for Class V Students Muhammadiyah 18 Palembang Elementary School - Winata, Fembi; Handayani, Widya; Putri, Siti Ayu Risma (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to determine the anxiety factor in doing floor exercise (front roll) for fifth grade students at SD Muhammadiyah 18 Palembang. The focus of this study was to evaluate the student’s anxiety factor in doing the front roll floor gymnastics who still experience a lot of doubts, or excessive anxiety in doing the front roll movement. This study uses the CIPP model which includes three indicators as follows: context, input, process, product. The interviews included fifth grade students at Muhammadiyah Elementary School and two sports teachers. Direct observation of the school and the infrastructure used by these students. This research was the cause of failure due to students’ anxiety in doing the floor gymnastics practice and there were also those who did not want to participate at all. So that it results in a student learning system that is not as expected. The results of context research are 59% input 40% process 40% product 48%.